2021
DOI: 10.17344/acsi.2020.6446
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Anticancer Evaluations of Novel Thiazole Derivatives Derived from 4-Phenylthiazol-2-amine

Abstract: Many novel thiazole derivatives were designed and synthesized using 4-phenylthiazol-2-amine. The reactivity of the latter compound toward different chemical reagents was studied. The structure of the newly synthesized compounds was established based on elemental analysis and spectral data. Furthermore, twenty compounds of the synthesized systems were selected and evaluated in (μM) as significant anticancer agents towards three human cancer cell lines [MCF-7 (breast adenocarcinoma), NCI-H460 (non-small cell lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…In this present study, and due to the remarkable role of pyrazolo [1,5-a]quinazoline, thiazole, and thiophene as anticancer agents in many pharmaceutical drugs, and in continuation of our interest and according to our previous reports [17][18][19][20][21][22][23][24][25] a number of novel bioactive systems were synthesized. The later products that were prepared underwent multi-component reactions, followed by their estimation for six cancer cell lines compared to the standard reference Foretinib.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…In this present study, and due to the remarkable role of pyrazolo [1,5-a]quinazoline, thiazole, and thiophene as anticancer agents in many pharmaceutical drugs, and in continuation of our interest and according to our previous reports [17][18][19][20][21][22][23][24][25] a number of novel bioactive systems were synthesized. The later products that were prepared underwent multi-component reactions, followed by their estimation for six cancer cell lines compared to the standard reference Foretinib.…”
Section: Introductionmentioning
confidence: 87%
“…1 H NMR (δ, ppm): 0.95-1.05 (s, 6H, 2CH3), 2.22 (s, 2H, CH2), 3.86 (s, 3H, OCH3), 6.77 (s, 1H, =CH), 7.04-7.99 (m, 9H, C6H5, C6H4). 13 (5,5-dimethyl-3-phenyl-2-thioxo-2,3,5,6-tetrahydrobenzo[d]thiazol-7(4H)ylidene)hydrazinyl)acetonitrile (24). To a solution of compounds 18 (2.89 g, 0.01 mol) in ethanol/DMF (15/5 mL), 2-cyanoacetohydrazide 23 (0.99 g, 0.01 mol) was added.…”
Section: General Procedures For the Synthesis Of 8-amino-55-dimethyl-...mentioning
confidence: 99%
“…Our previous work demonstrated that many of the synthesized compounds were useful in future drug designing. [23][24][25][26] In continuation of the previous work we are describing here a rapid and efficient preparation of a set of new benzo [d] thiazole derivatives starting from ortho-aminothiophenol that reacted with either ethyl cyanoacetate, diethylmalonate or ethyl acetoacetate. This new approach enables more rapid generation of a higher number of benzo [d]thiazole derivatives that were obtained using simple reactions using readily available reagents.…”
Section: Introductionmentioning
confidence: 99%
“…The current study constitutes a further thread in green organic chemistry and one-pot multi-component reactions (MCRs); it aims to improve the synthetic procedures of various prepared compounds. [26][27][28][29][30] Herein preparations of many 5,6,7,8-tetrahydrobenzo[b]pyrans are described through multi-component reactions and via other simple methods. The obtained products were tested on three human tumor cell lines, including A-549 (lung carcinoma), HC-29 (colorectal adenocarcinoma), and MKN-45 (gastric cancer).…”
Section: Introductionmentioning
confidence: 99%